âI school atâ¦â and Other Sentences: A Phenomenon of English Sentence Production of Indonesian EFL Learners - Eli Indriyani, Christina; Septiyani, Maria Septiyani (Berumpun, 2018)
Learning English as a foreign language is important but it is also difficult. The reason why it is important is that it can support learners to reach the opportunities in the future, for example getting a job, getting a scholarship, conducting a research and many others. However, it is also difficult. The difficulties can be seen from various aspects, such as learnersâ background knowledge, learnersâ mother tongue, and learnersâ anxiety. Indonesian who learn English experiences these kinds of difficulties. English is learnt as a foreign language in Indonesia. Though it has taught since early level, there are mistakes found by the writers when the learners produce spoken or written utterances. The mistake that triggers the writers to write this paper is the sentence âI am school at SMA 5 Kupang,â when the student meant to say âSaya bersekolah di SMA 5 Kupang.â This kind of mistake raises since the students do not get used to English and they have lack of knowledge of English. Therefore, instead of saying âI study at SMA 5 Kupang,âthey say âI am school at SMA5 Kupang.â This phenomenon likely influence studentsâ ability in producing utterances especially in direct translation. The data of this research was collected through observation and studentsâ performance in class. The data was analysed qualitatively and the result showed that most students made mistakes before the teachers correct them. This paper aims to dig out more on this phenomenon and it is expected to give more insight to the English learning and teaching process.